2021
DOI: 10.18409/ispiv.v1i1.184
|View full text |Cite
|
Sign up to set email alerts
|

PIV measurements of entrainment process of directly injected media in internal combustion engines

Abstract: PIV measurements have been successfully applied to various flow fields relating internal combustion engines such as in-cylinder air motion, air flow in an intake port, and even a discharging passage of an ignition plug. Measurements of induced air motion around diesel sprays can be said to be a significant example of the PIV applications because the air motion is reflected in an unsteady complicated flow structure. Instead of the apparent entrainment exaggerated by spray droplet dispersing, substantial air ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The utilization of planar particle image velocimetry (PIV) technique has facilitated the measurement of instantaneous air velocities, and the calculation of spatial derivative properties. In [19] PIV measurements have been applied to study mixture entrainment process of torch flames typical of prechamber engines. Results showed that the air entrainment rate is directly proportional to the injection pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of planar particle image velocimetry (PIV) technique has facilitated the measurement of instantaneous air velocities, and the calculation of spatial derivative properties. In [19] PIV measurements have been applied to study mixture entrainment process of torch flames typical of prechamber engines. Results showed that the air entrainment rate is directly proportional to the injection pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Marine Heavy Fuel Oil (HFO) is mainly derived from the residue leftover after refining crude oil, providing an economical choice for ship fuel because of its lower price [7]. Meanwhile, The shipping industry emissions reached 2.89% of worldwide anthropogenic CO2 emissions in 2018, according to the Fourth International Maritime Organization (IMO) GHG Study in 2020 [8,9]. MARPOL Annex VI had advised that the IMO strictly regulated the emissions to minimize NOx emissions by 75% in Tier III.…”
Section: Introductionmentioning
confidence: 99%